Bridging the Gap: The Role of Monitoring and Evaluation in Evidence-Based Policy Making (United Nations Children's Fund (UNICEF), 2010)
Monitoring and evaluation has a strategic role to play in informing policy making processes. This document. titled Bridging the gap. The role of monitoring and evaluation in Evidence-based policy making was written with the aim of improving relevance, efficiency and effectiveness of policy reforms. It putsfoward a number of strong contributions from senior officers in institutions dealing with Evidence-based policy making.